2019
DOI: 10.1088/1674-1056/ab4274
|View full text |Cite
|
Sign up to set email alerts
|

Cluster structure prediction via CALYPSO method*

Abstract: Cluster science as a bridge linking atomic molecular physics and condensed matter inspired the nanomaterials development in the past decades, ranging from the single-atom catalysis to ligand-protected noble metal clusters. The corresponding studies not only have been restricted to the search for the geometrical structures of clusters, but also have promoted the development of cluster-assembled materials as the building blocks. The CALYPSO cluster prediction method combined with other computational techniques h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 112 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…The crystal structure analysis by particle swarm optimization (CALYPSO) developed by Wang et al, [173,174] was built on another classic search algorithm called particle swarm optimization (PSO). CALYPSO had been successfully applied in the design of various materials structures such as 3D crystals, [174] clusters, [175] and 2D materials. [176] Other algorithms that have been applied in materials structures search includes the ab initio random structure searching (AIRSS), [177] simulated annealing, [178][179][180] basin hopping, [181][182][183] and minima hopping.…”
Section: Structures Searchingmentioning
confidence: 99%
“…The crystal structure analysis by particle swarm optimization (CALYPSO) developed by Wang et al, [173,174] was built on another classic search algorithm called particle swarm optimization (PSO). CALYPSO had been successfully applied in the design of various materials structures such as 3D crystals, [174] clusters, [175] and 2D materials. [176] Other algorithms that have been applied in materials structures search includes the ab initio random structure searching (AIRSS), [177] simulated annealing, [178][179][180] basin hopping, [181][182][183] and minima hopping.…”
Section: Structures Searchingmentioning
confidence: 99%
“…For example, random search provides an unbiased configuration sampling [7] while genetic algorithm combines and propagates useful structural markers [8,9]. Basin-hopping [10,11] represents an efficient technique for escaping from local minima and mapping the potential energy surface (PES) and particle swarm optimization [12,13] relies on the population information for navigating the energy landscape. However, when these techniques are combined with ab-initio methods for the description of inter-atomic interaction, they become computationally expensive and result in an insufficient sampling of PES [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…With so many interesting phenomena associated with tm-doped B clusters, it is interesting to see what happens when B clusters are doped with Rb atoms, which are alkali metals. 38,39…”
Section: Introductionmentioning
confidence: 99%
“…35 In addition, there are many medium-sized doped boron clusters with interesting structural evolution. 36,37 In the CALYPSO based cluster structure prediction study of Tian's group, we found that they mentioned a number of interesting phenomena for metal-doped boron clusters with Li 2 B 24 tubular structures, MgB 18 drum-like tubular clusters, BeB 38,39 The properties and geometry of atomic clusters are sizedependent and highly sensitive to the nature of the dopant. [40][41][42] Yang's group searched for the structure of the Cs 2 B n (n = 1-12) clusters using unbiased crystal structure analysis and determined the global minimum.…”
Section: Introductionmentioning
confidence: 99%